Effectiveness of Combination Gel of Bilimbi Leaf and Aloe Vera Extract for Healing Burns in Male White Rats - Sara Nurmala; Marybet Tri Retno Handayani; Dian Fatimah Hartoyo (Poltekkes Kemenkes Tanjung Karang, 2025)
Burns are a global public health problem, with approximately 180,000 deaths each year. The incidence of second-degree burns in Indonesia accounts for 46.7%. Redness, swelling, ulcers, and severe pain characterize these wounds. This study aims to test the effectiveness, percentage of healing, and length of gel application of a combination of star fruit leaf extract and aloe vera leaf pulp on the healing of second-degree burns in male rats. Morton's method was used in this study to measure the diameter of the burn wound. The treatments of this study included a combination gel of star fruit leaf extract and aloe vera leaf with variations in the ratio of F1 (6%: 5%), F2 (6%: 10%), F3 (12%: 5%), and the control group with 5 replicates each group. The results showed that the gel combination of extracts of star fruit leaves and aloe vera leaves effectively treated burn wounds in rats. Duncan's test of the treatment of variations in extract concentration showed a significant difference. The combination of starfruit leaf extract and aloe vera in gel preparation has effectively healed burns in male mice. The duration of administration is 16 days, with the percentage of healing for categories F1, F2, and F3 being 45%, 55%, and 61%, respectively. Burn wound healing activity occurs because the two extracts used contain alkaloids, flavonoids, saponins, and tannins, which act as anti-inflammatories, increase the growth of epithelial cells and collagen, and help the formation of new tissues.